2022
DOI: 10.1007/s40123-022-00504-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Changes After Intravitreal Fluocinolone Acetonide Implant: Results from Four European Countries

Abstract: Introduction The 0.19 mg fluocinolone acetonide (FAc) intravitreal implant delivers a continuous intravitreal corticosteroid dose for the treatment of refractory diabetic macular oedema (DMO). The aim of this study was to assess the impact of an FAc intravitreal implant on intraocular pressure (IOP). Methods We retrospectively collected anonymised data on the patients’ characteristics, DMO treatment, and IOP and IOP-lowering treatments before and after the FAc intravitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our patient underwent 7 DEX-IVI before the first FAc-IVI. A recent study also confirmed that the mean IOP remained normal during the first year after FAc-IVI and that OHT was successfully managed with topical IOP-lowering therapy most of the time [13]. Patients with IOP-lowering therapy before the FAc-IVI seem to be more likely to have additional IOP-lowering treatments during the 12-month follow-up [13].…”
Section: Discussionmentioning
confidence: 84%
“…Our patient underwent 7 DEX-IVI before the first FAc-IVI. A recent study also confirmed that the mean IOP remained normal during the first year after FAc-IVI and that OHT was successfully managed with topical IOP-lowering therapy most of the time [13]. Patients with IOP-lowering therapy before the FAc-IVI seem to be more likely to have additional IOP-lowering treatments during the 12-month follow-up [13].…”
Section: Discussionmentioning
confidence: 84%
“… 212 Similarly, in another study with patient data obtained from 4 European countries, it showed that in 1 year follow-up of patients who received fluocinolone acetonide implant, 24.4% of them developed significant IOP elevation. 153 …”
Section: Clinical Science Review Of Gig/giohtmentioning
confidence: 99%
“…212 Similarly, in another study with patient data obtained from 4 European countries, it showed that in 1 year follow-up of patients who received fluocinolone acetonide implant, 24.4% of them developed significant IOP elevation. 153 Intracameral injection (delivery to the anterior chamber) and suprachoroidal injection (delivery to the suprachoroidal space) are also used for GC administration. 211 Mataftsi et al concluded that intracameral injection of preservative-free DEX did not increase the risk of GIOHT/GIG in pediatric patients after cataract surgery.…”
mentioning
confidence: 99%